Model Hidden Curiculum di Pondok Pesantren Nurul Haramain Putra NW Narmada - Ramli Ahmad (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
Hidden curriculum is curriculum that doesn't studied, This clear No can visible (faint), latent, and constitutive results from non academic schools, curriculum This is agreed values, shared strategy experienced participant educated educator and can made reflecting tradition kind so that produce Act appropriate behavior with code ethics learning. The purpose of this research is For know about How aspect structural and cultural, the forms and models of the hidden curriculum in Islamic boarding schools Nurul Haramain Putra NW Narmada Islamic Boarding School. Type research Which used is study field with approach qualitative. The types of data collected in this study are primary and secondary data. Method collection data use method observation, interview and documentation. Steps For analyze is data conventions, data presentation and conclusions. The results of this study are the hidden curiculum aspects contained in the Nurul Haramain Putra NW Narmada Islamic Boarding School which are divided into two, namely structural aspects and cultural aspects. Musharifah, providing reinforcement of material that has been studied in class that the Santri have not understood by the ustadzah, Mahfudzot, is the reading of Arabic or English proverbs that can increase the interest in learning Santri, and the hidden curriculum model at Pondok Pesantren Nurul Haramain Putra NW Narmada can be seen in all activities the Santri for 24 hours, the activities carried out are dominated by a hidden curriculum whose implementation is the responsibility of the Santri who are administrators of the Santri Nurul Haramain Organization (OSNH), but are still guided and fostered by ustadz and ustadzah.